2014
DOI: 10.1007/s10841-014-9717-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecological restoration on Orthoptera assemblages in a Mediterranean steppe rangeland

Abstract: International audienceIn the last century, human activities have contributed to the fragmentation and the loss of 80 % of the original surface of a Mediterranean steppe rangeland in southeastern France. In a recent ecological restoration project, an intensively cultivated orchard of 357 ha planted in 1987 among the steppe vegetation was rehabilitated as a herbaceous habitat for steppe birds after its abandonment in 2006. In addition, three experimental restoration treatments (nurse species seeding, hay transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Higher abundance of Diptera in pasture monocultures has been reported previously 42 , 43 . Composition of Orthoptera communities is known to be greatly affected by plant cover 44 and changes of environmental conditions, forming distinct communities characteristic of areas with low vegetational cover and others characteristic of high vegetation cover 45 47 . Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher abundance of Diptera in pasture monocultures has been reported previously 42 , 43 . Composition of Orthoptera communities is known to be greatly affected by plant cover 44 and changes of environmental conditions, forming distinct communities characteristic of areas with low vegetational cover and others characteristic of high vegetation cover 45 47 . Some studies have reported that abundance of some groups falls with habitat simplification 48 , while in other groups abundance increases 49 which was also recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Unmanaged steppe could enhance the abundance and diversity of Orthoptera assemblages (herbivores) compared with managed grasslands in Mediterranean steppe rangeland (Alignan, Debras, & Dutoit, ). However, Goodenough and Sharp () also found that moderate grazing intensity in both autumn and winter could enhance the abundance of butterflies while having disadvantageous effects on plants in winter (Goodenough & Sharp, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean Basin, arthropods, such as spiders (García et al 2009), beetles (Alignan et al 2018b) and Orthoptera (Alignan et al 2014(Alignan et al , 2018a Lortie et al (2004). Each process/filter is represented by a double horizontal line and the corresponding description is in italics on their left.…”
Section: Grassland Invertebratesmentioning
confidence: 99%
“…In the Mediterranean Basin, arthropods, such as spiders (García et al 2009), beetles (Alignan et al 2018b), and Orthoptera (Alignan et al 2014, 2018a) are used as bioindicators of restoration success because of their high sensitivity to changes in vegetation structure (height and density) or composition. Continuing to explore plant‐arthropod relationships and ecosystem engineers, such as ants and earthworms, will contribute to a more integrative response for overcoming key constraints in NwMedB grassland restoration.…”
Section: Conclusion and Research Perspectivesmentioning
confidence: 99%